Answer:
2.5
Step-by-step explanation:
Simplifying
2y + -1.7 = 3.3
Reorder the terms:
-1.7 + 2y = 3.3
Solving
-1.7 + 2y = 3.3
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '1.7' to each side of the equation.
-1.7 + 1.7 + 2y = 3.3 + 1.7
Combine like terms: -1.7 + 1.7 = 0.0
0.0 + 2y = 3.3 + 1.7
2y = 3.3 + 1.7
Combine like terms: 3.3 + 1.7 = 5
2y = 5
Divide each side by '2'.
y = 2.5
Simplifying
y = 2.5
Given: 11-pound mixture of peanuts, almonds, and raisins
Cost:
peanuts - 1.5 per pound
almonds - 3 per pound
raisins - 1.5 per pound
mixture:
twice as many peanuts as almond; total cost of mixture is 21.
a + p + r = 11 lbs
a + 2a + r = 11 lbs
3a + r = 11
r = 11 - 3a
1.5(2a) + 3a + 1.5r = 21
3a + 3a + 1.5r = 21
6a + 1.5r = 21
6a + 1.5(11-3a) = 21
6a + 16.5 - 4.5a = 21
6a - 4.5a = 21 - 16.5
1.5a = 4.5
1.5a/1.5 = 4.5/1.5
a = 3
almonds = 3 lbs
peanuts = 2a = 2(3) = 6lbs
raisins = 11 - 3a = 11 - 3(3) = 11 - 9 = 2 lbs
<span>My answer is: C. 6 lbs peanuts, 3 lbs almonds, 2 lbs raisins </span>
D(X+2)(2X+1) This is your answer.
Answer:
290
Step-by-step explanation: